Men and COVID-19: Adding a gender lens. Issue 7 (2nd July 2020) - Betron, Myra; Gottert, Ann; Pulerwitz, Julie; Shattuck, Dominick; Stevanovic-Fenn, Natacha
ABSTRACT: In this commentary, the authors point out that there are important gender determinants to both men's and women's vulnerabilities to COVID-19, and call on the global health community to unpack and address these early in the COVID-19 pandemic response. They point to best practices and tools from two decades of engaging men in research and programming in the sexual and reproductive health field.